Candida auris Forms High-Burden Biofilms in Skin Niche Conditions and on Porcine Skin - Mark V. Horton (American Society for Microbiology, 2020)
ABSTRACT Emerging pathogen Candida auris causes nosocomial outbreaks of life-threatening invasive candidiasis. It is unclear how this species colonizes skin and spreads in health care facilities. Here, we analyzed C. auris growth in synthetic sweat medium designed to mimic axillary skin conditions. We show that C. auris demonstrates a high capacity for biofilm formation in this milieu, well beyond that observed for the most commonly isolated Candida sp., Candida albicans. The C. auris biofilms persist in environmental conditions expected in the hospital setting. To model C. auris skin colonization, we designed an ex vivo porcine skin model. We show that C. auris proliferates on porcine skin in multilayer biofilms. This capacity to thrive in skin niche conditions helps explain the propensity of C. auris to colonize skin, persist on medical devices, and rapidly spread in hospitals. These studies provide clinically relevant tools to further characterize this important growth modality. IMPORTANCE The emerging fungal pathogen Candida auris causes invasive infections and is spreading in hospitals worldwide. Why this species exhibits the capacity to transfer efficiently among patients is unknown. Our findings reveal that C. auris forms high-burden biofilms in conditions mimicking sweat on the skin surface. These adherent biofilm communities persist in environmental conditions expected in the hospital setting. Using a pig skin model, we show that C. auris also forms high-burden biofilm structures on the skin surface. Identification of this mode of growth sheds light on how this recently described pathogen persists in hospital settings and spreads among patients.